When Egypt Went Broke: A Novel - Day, Holman, 1865-1935 (Salt Lake City, UT : Project Gutenberg, 2006)
"When Egypt Went Broke: A Novel" by Holman Day is a fictional narrative likely written during the early 20th century. The story is set in a town named Egypt and revolves around the character Tasper Britt, who is depicted as a powerful moneylender, sometimes referred to as "Phay-ray-oh." As the narrative unfolds, it hints at themes of ambition, societal power dynamics, and personal aspirations, particularly through Britt$1 (Bs attempts to gain political honor and reclaim his reputation in a community that views him with disdain. The opening of the novel introduces us to Tasper Britt$1 (Bs daily life, showcasing his routines and inner thoughts as a widower seeking to redefine himself after the death of his wife, Hittie. Britt$1 (Bs actions are influenced by his desire to impress a young woman named Vona Harnden, who works in his bank. The narrative captures his blend of vanity, ambition, and a newfound sense of freedom that leads him to aspire for political promotion in a town plagued by debt and hardship. As tensions rise around Britt's controversial status in the town, the introduction of other characters, including his brother Usial and the Prophet Elias, sets the stage for conflicts that explore the consequences of greed and the dynamics of brotherhood in a struggling community. (This is an automatically generated summary.)s
Release date is 2006-04-13
Produced by Dagny; John Bickers; David Widger
Keywords: Fiction